The Influence of Online Customer Reviews, Online Customer Ratings, Convenience, and Trust on Product Purchase Decisions on the Shopee Application among Students in Purwokerto - Davita Putri Azaria; Wisnu Wijayanto; Akbar Pahlevi (Darul Yasin Al Sys, 2026)
The rapid growth of e-commerce has transformed consumer purchasing behavior in online environments, particularly under conditions of information asymmetry and transaction uncertainty. In such contexts, consumers increasingly rely on online customer reviews, online customer ratings, platform convenience, and marketplace trust as evaluative cues in making purchase decisions. This study aimed to examine the influence of online customer reviews, online customer ratings, convenience, and trust on purchase decisions among university students using the Shopee application in Purwokerto. A quantitative approach with a survey method was employed, involving 100 respondents selected through purposive sampling. The respondents were students who had completed at least two purchases on Shopee within the previous six months. Data were collected through questionnaires and analyzed using multiple linear regression. The findings reveal that online customer reviews, online customer ratings, convenience, and trust each have a positive and significant effect on purchase decisions. Among these variables, convenience emerged as the most influential determinant of purchasing behavior. The coefficient of determination indicates that the four independent variables collectively explain 77.7% of the variance in purchase decisions. The study concludes that information quality, platform usability, and consumer trust are critical factors shaping online purchasing decisions in e-commerce environments. These findings contribute to the literature on digital consumer behavior by demonstrating the combined role of informational, functional, and relational factors in purchase decision-making, while offering practical implications for e-commerce platforms to optimize review and rating systems, improve user convenience, and strengthen consumer trust to sustain competitiveness in the digital marketplace.